Health economic evaluation of an mRNA high-risk human papillomavirus (HR-HPV) assay versus a DNA HR-HPV assay for the proposed French cervical screening programme. Issue 29 (22nd July 2022) - Dombrowski, Caroline A.; Weston, Georgie MF; Descamps, Pr Philippe; Izopet, Pr Jacques; Adams, Elisabeth J.; Adams, Elisabeth
Abstract : Objective: Population screening programmes must make good use of resources for the health system and users. To evaluate impacts of the type of diagnostic test in the new French cervical screening programme, an messenger ribonucleic acid (mRNA) high-risk human papillomavirus assay was compared to a deoxyribonucleic acid (DNA) high-risk human papillomavirus assay for a hypothetical cohort of women aged 25 to 65 years. Perspective: This evaluation takes the perspective of the French healthcare system. Setting: France Methods: A decision tree model reflecting the French cervical screening algorithms was parametrised using French cost and population data and the Danish Horizon study. The outcomes were total costs, and number of colposcopies, HPV tests and cytology tests for the cohort. One-way and probabilistic sensitivity analyses and scenarios analyses were conducted to test the robustness of results to parameter and structural uncertainty. Results: Adopting an mRNA versus DNA assay as part of national cervical screening in France is estimated to save €6.5 million (95% credibility intervals €-1.3 - €13.5 million) and prevent 47, 795 (95% credibility intervals 35, 309 - 60, 139) unnecessary colposcopies, 38, 666 unnecessary HPV tests and 121, 670 cytology tests over two years for a cohort of 2, 168, 806 million women aged 25 to 65 years. Sensitivity analyses indicated robust results across a range of inputs. Conclusion: The choice of high-risk human papillomavirus assay makes a significant difference to resource use and costs and is important to consider when implementing cervical screening in France. Using an mRNA versus DNA assay can result in cost savings and reductions in unnecessary testing and procedures, which in turn benefits women and the health care system.